Diminishing discoloration; enhancing esthetics: Management of discolored restorations with computer-aided-design/computer-aided-manufacturing veneers - Rishu Koul; Deepak Kalia; Kamal Verma (Journal of Oral Research and Review)
Tooth discoloration that cannot be treated with more conservative procedures such as bleaching or microabrasion, requires restorative treatment to mask the unesthetic appearance. Ceramic veneers provide exceptional resistance to wear and abrasion, retain their glazed luster over a very long time, and are durable. This case report presents the rehabilitation of a patient with discolored composite restorations on maxillary anterior teeth with zirconia veneers fabricated using computer-aided-design/computer-aided-manufacturing technology.